HOW NEUROLINGUISTIC FACTORS AFFECT SECOND LANGUAGE ACQUISITION - Suyunova Mohinur Ilxom qizi (Western European Studies, 2024)
In this day and age of globalization and liberalization, English is the only global lingua franca. The English language is a valuable tool for learning new technical information. In this environment, both English students and teachers suffer significant psychological challenges. Neurolinguistics is the study of brain mechanisms and how the brain performs in linguistic competencies. The brain controls motor and sensory activity, as well as the process of thinking. Research on brain development supports an anatomical and psychological approach to language development. NLP focuses on psychological and neurological variables. It also discusses how the brain works and how to train it for specific tasks. A variety of techniques are employed in NLP. It enhances both fluency and accuracy in the target language. It helps non-native speakers to improve their LSRW skills. This paper discusses the importance of NLP in language learning and teaching. It also covers the advantages and disadvantages of NLP for learning. Neuro-linguistic programming motivates self-correction and provides solutions for overcoming issues
Keywords: neurolinguistic programming; language acquisition